الشيخ عبد الرزاق دربال السوفي وجهوده في الدعوة و الاصلاح - فطحيزة عمار, إيمان; طويل, صديقة (University of Eloued-جامعة الوادي, 2022)
"لقد تناولنا في بحثنا هذا بالتحليل والوصف والجمع جهود الشيخ عبد الرزاق دربال في الدعوة والإصلاح التي قمنا بها في منطقة الرباح ،ولهذا عرفنا الحياة الشخصية للشيخ عبد الرزاق دربال ( مولد ونشأته ونسبه ، صفاته وأسرته ومرضه ووفاته ) وعرجنا على أبرز محطات حياته التعلمية والتعليمية والسياسية والدينية والخيرية والاجتماعية وكما بينا ما كان يقوم به الشيخ عبد الرزاق دربال من أعمال إنسانية مبادرات خيرية وإصلاحات اجتماعية ومناضلات سياسية بارزة ، ولم نغفل مع كل ذلك على ذكر دوره في الجهود الدعوية والإصلاحية ودوره في جمعية الإصلاح والإرشاد . وبذلك حاولنا أن نكون صورة متقاربة عن الشيخ عبد الرزاق دربال وجهوده في الدعوة والإصلاح وأثر ذلك على الفرد والمجتمع .""In this research, wehave analyzed, described and collected the efforts of Sheikh Abd al-Razzeq Derbal in advocacy and reform that we carried out in the Al-Rabah area, and for this we learned the personal life of Sheikh Abd al-Razzeq Derbal(birth, upbringing , lineage, characteristics, family, illness and death.)and we reviewed the most prominent stage of his educational, educational and political life and religious , charitable, and social work, and as we have shown, what humanitarian work Sheikh Abd al-Razzeq Derbal was doing, charitable initiatives, social reforms and prominent political struggles, and we did not neglect will all that to mentionhis role in advocacy and reform efforts and his role in the Association of reform and guidance . Thus , we tried to form a close picture of Sheikh Abd al-Razzeq Derbal and his efforts in advocacy and reform and the impact of that on the individual and society ."
مذكرة ماستر
Keywords: الدعوة – عبد الرزاق دربال – الإصلاح – الرباح .; Invitation- Abd al-Razzeq Derbal -Reform - Al-Rabah